Microbial Biogeography Along the Gastrointestinal Tract of a Red Panda - Zeng, Yan; Zeng, Dong; Zhou, Yi; Niu, Lili; Deng, Jiabo; Li, Yang; Pu, Yang; Lin, Yicen; Xu, Shuai; Liu, Qian; Xiong, Lvchen; Zhou, Mengjia; et al. (Frontiers in Microbiology, 2018)
The red panda (Ailurus fulgens) is a herbivorous carnivore that is protected worldwide. Gastrointestinal tract (GIT) microbial community has been widely acknowledged of its vital role in host health, especially in diet digestion. However, no study to date has revealed the GIT microbiota in the red panda. Here, we characterized the microbial biogeographical characteristics in the GIT of a red panda using high-throughput sequencing technology. Significant differences were observed among GIT segments by beta diversity of microbiota, which were divided into four distinct groups: the stomach, small intestine, large intestine, and faecal. The stomach and duodenum showed less bacterial diversity, but contained higher bacterial abundance and the most unclassified tags. The number of species in the stomach and small intestine samples was higher than that of the large intestine and faecal samples. A total of 133 core operational taxonomic units (OTUs) were obtained from the GIT samples with 97% sequence identity. Proteobacteria (52.16%), Firmicutes (10.09%), and Bacteroidetes (7.90%) were the predominant phyla in the GIT of the red panda. Interestingly, Escherichia-Shigella exhibited relatively large abundances in the stomach, small intestine, and faecal whereas the abundance of Bacteroides in the large intestine was high. Overall, our study provides a first understanding of the gut biogeography of the red panda microbial population. Future research will be important to investigate the microbial culture, metagenomics and metabolism of red panda GIT, especially in Escherichia-Shigella.